Temporal and Spatial Genetic Population Structure of Cryphonectria parasitica and Its Associated Hypovirus Across an Invasive Range of Chestnut Blight in Europe - Ježić, Marin; Schwarz, Janine Melanie; Prospero, Simone; Sotirovski, Kiril; Risteski, Mihajlo; Ćurković-Perica, Mirna; Nuskern, Lucija; Krstin, Ljiljana; Katanić, Zorana; Maleničić, Ema; Poljak, Igor; Idžojtić, Marilena; et al. (Scientific Societies, 2021)
Chestnut blight has spread throughout Europe since the introduction of its causal agent, Cryphonectria parasitica, >70 years ago. In our study, we analyzed the diversity of vegetative compatibility (vc) and microsatellite genotypes of C. parasitica, as well as sequence diversity of Cryphonectria hypovirus 1 (CHV1) in six populations from Switzerland, Croatia, and North Macedonia. Resampling of local populations that were already investigated more than a decade ago allowed us to analyze the spatial and temporal population structure across an invasive range of the pathogen in Europe. Regardless of which genetic marker was used, the >60-year-old Swiss and Croatian populations had high population diversity, whereas more recent North Macedonian populations were mostly clonal. These diversity differences between the investigated populations remained stable over time. A high diversity of CHV1 was observed in all three countries, with North Macedonian strains forming a separate cluster from strains obtained in other countries. No correlation between vc diversity and CHV1 prevalence was observed, suggesting a well-established and maintained natural hypovirulence in all countries, further corroborated by an observed increase in genetic diversity of Croatian C. parasitica populations over time, without collapse of CHV1 prevalence.